Internal Factors Causing Misunderstanding Towards Islam and Islamic Law - Eko Cipta Burnama; Ali Romon; Neneng Nurhasanah (SEAN Institute, 2025)
Misunderstandings of Islam remain a pervasive global phenomenon, affecting both interreligious perceptions and intra-faith comprehension. While Islam fundamentally promotes justice, compassion, and peace, it is frequently portrayed as intolerant, violent, or irrational. In Indonesia—the world’s largest Muslim-majority country—such misconceptions have intensified, evidenced by public ridicule and the derogatory representation of Islamic symbols, including distorted references to Allah and the Prophet Muhammad. This study identifies that internal factors among Muslims significantly contribute to the persistence of these misperceptions. Employing a qualitative-analytical approach, this study integrates several theoretical frameworks: Ninian Smart’s dimensions of religion, Schramm’s communication model, Berger and Luckmann’s theory of social construction, Edward Said’s Orientalism, and Gudykunst and Kim’s intercultural communication theory. The findings reveal five core internal factors: (1) fragmented understanding of Islamic teachings that privileges textual over contextual interpretations; (2) limited exegesis that neglects socio-political dimensions; (3) epistemological tensions between rationalist (Ahl al-Ra’y) and traditionalist (Ahl al-Hadith) schools; (4) political instrumentalization of religion; and (5) insufficient religious education that impairs critical engagement with Islamic values. These internal conditions are reinforced by external media narratives and orientalist discourse, perpetuating negative stereotypes and Islamophobia. This article argues for the urgent need to reconstruct Islamic understanding through contextualized education, interfaith dialogue, and inclusive hermeneutics that reflect Islam’s ethical and universal dimensions. Such efforts are essential to deconstruct entrenched biases and to foster more accurate, respectful representations of Islam in both Muslim and non-Muslim societies.